4v+2-2(-8v-1)=2(v-3)

Simple and best practice solution for 4v+2-2(-8v-1)=2(v-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4v+2-2(-8v-1)=2(v-3) equation:


4v+2-2(-8v-1)=2(v-3)

We simplify the equation to the form, which is simple to understand
4v+2-2(-8v-1)=2(v-3)

Reorder the terms in parentheses
4v+2+(+16v+2)=2*(v-3)

Remove unnecessary parentheses
+4v+2+16v+2=+2+*(+v-3+)

Reorder the terms in parentheses
4v+2+16v+2=+(+2v-6)

Remove unnecessary parentheses
+4v+2+16v+2=+2v-6

We move all terms containing v to the left and all other terms to the right.
+4v+16v-2v=-6-2-2

We simplify left and right side of the equation.
+18v=-10

We divide both sides of the equation by 18 to get v.
v=-0.55555555555556

See similar equations:

| X(.75)=3 | | -2+2x=-3+7x | | 45=24(-7X) | | 45=24-7X | | 2=-z/8+13 | | 55-2x=10-7x | | 32-4x=8(-5x-5) | | 24-16x=-12x | | 5p-5=30 | | 2x-9-6x=-7x+5x | | 2x+5=-44-5x | | 6x+9=9x+6 | | =v^2+2v-8 | | -2p-36=-4(-6+8p) | | -4.2=-0.84(m+4) | | -8w+14=0 | | 7y=9x+6 | | x(x-3)=x^2+6x+8 | | 8x-(6x-3)=17 | | 84=-7+7(a+5) | | 1/3(b-3)=6 | | -4v-1=0 | | p^2q^2=36 | | -4*6+6y=-24 | | -5p+20=25 | | 3x^4*2w^4x^5*8w=x | | 1(b-3)=6 | | 3y-12+63=180 | | 2x-(-15)=27-4x | | x/7-22=-1 | | 3x-7x-9=4x+4-9 | | (y-7)-(y+5)=8y |

Equations solver categories